2021
DOI: 10.3390/electrochem3010001
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advancements in the Synthesis and Application of Carbon-Based Catalysts in the ORR

Abstract: Fuel cells are a promising alternative to non-renewable energy production industries such as petroleum and natural gas. The cathodic oxygen reduction reaction (ORR), which makes fuel cell technology possible, is sluggish under normal conditions. Thus, catalysts must be used to allow fuel cells to operate efficiently. Traditionally, platinum (Pt) catalysts are often utilized as they exhibit a highly efficient ORR with low overpotential values. However, Pt is an expensive and precious metal, posing economic prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 148 publications
0
13
0
Order By: Relevance
“…21 The texture and pore size resulting in the synthesis method plays a significant role in providing robust catalytic support for fuel cell applications. 22 Alegre et al 18 demonstrated that it is possible to minimize the rate of mass transfer at the catalyst layer based on the special pore texture of the modifiable carbon. The potential uses of organic aerogels have led to studies linked to their synthesis and use in the commercial and scientific.…”
Section: F I G U R E 1 History Of Fuel Cell Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…21 The texture and pore size resulting in the synthesis method plays a significant role in providing robust catalytic support for fuel cell applications. 22 Alegre et al 18 demonstrated that it is possible to minimize the rate of mass transfer at the catalyst layer based on the special pore texture of the modifiable carbon. The potential uses of organic aerogels have led to studies linked to their synthesis and use in the commercial and scientific.…”
Section: F I G U R E 1 History Of Fuel Cell Technologymentioning
confidence: 99%
“…Interestingly, almost all of the outcomes of research revealed that organic aerogels used as catalyst supports in low‐temperature fuel cell applications stabilize nano‐sized metal particles, resulting in a strong catalytic action 21 . The texture and pore size resulting in the synthesis method plays a significant role in providing robust catalytic support for fuel cell applications 22 . Alegre et al 18 demonstrated that it is possible to minimize the rate of mass transfer at the catalyst layer based on the special pore texture of the modifiable carbon.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesized catalytic material exhibited a broad diffraction peak at 2θ = 24.7 • , which corresponded to the (111) reflection plane, which is characteristic of the rGO_COOH carbon support [45]. After pyrolysis, the diffraction patterns of the catalyst (NFeC@rGO-COOH) appeared at angles of 17 210), (301), and (131) reflections, respectively, confirming the partial decomposition of PB during calcination, as well as the presence of additional coexisting phases Fe x C with the PB [46]. The obtained diffraction peaks are narrow, indicating the system's crystalline structure and the considerably large sizes of PB.…”
Section: Physicochemical Characterizationmentioning
confidence: 99%
“…Sadly, the scarce resources, high prices, and decreased activity of Pt in the presence of small organic compounds (crossover effect in applications towards alcohol fuel cells) make them difficult to use in commercial applications. As a consequence, it is still challenging to develop efficient non-precious metal or metal-free catalysts for ORR [10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…The past few years have witnessed H 2 /O 2 fuel cells gaining increasing popularity as a result of their high efficiency and environmental friendliness. However, a potential problem is associated with the slow kinetics of the ORR [73,74] that can be a hindrance for practical applications. In order to commercialize ORR technologies in the future, it is vital to develop efficient catalysts.…”
Section: Mofs For Fuel-cell Applications 21 Mofs As Electrode Applica...mentioning
confidence: 99%